Estudo dos aspectos tecnológicos e de qualidade envolvidos no aproveitamento da casca e da polpa da melancia (Citrullus Ianatus Schrad) - Freire, Julianne Viana (2009)
This study aimed to study and to model the drying process fresh and osmotically pretreated in sucrose solution watermelon (Citrullus lanatus S.). The osmotic dehydration process was studied through an experimental design, with independent variables as osmotic solution temperature (30 - 50oC) and concentration (40 - 60% w / w) and immersion time (90 - 240min), where the objective was to obtain a maximum water loss with a minimum solid gain. The convective drying was performed at various air drying temperatures (40 - 60oC). The best combination of variables obtained for the osmotic dehydration of watermelon pulp was: 300C, 60% w/w and 90 minutes. The highest drying rates were obtained for the pulp pre-treated osmotically when compared with the fresh one. The water effective diffusivities were in the order of 10-10m2/s, agreeing with the diffusivity of liquids. The empirical exponential model of two parameters fitted very well to the experimental data of both process. The Diffusional model fitted satisfactorily to the experimental data watermelon peels drying. The best drying conditions for the final products were 500C for the pulp pretreated osmotically and 600C for the fresh pulp and peels. Such products are considered source of protein and low lipid content foods, highlighting a significant amount of carotenoid (lycopene) to watermelon fresh pulp.